Cost-effectiveness of edoxaban vs low-molecular-weight heparin and warfarin for cancer-associated thrombosis in Brazil. Issue 196 (December 2020) - Lopes, Danilo G.; Tamayo, Arturo; Schipp, Bernhard; Siepmann, Timo
Abstract: Background: Venous thromboembolism (VTE) is the second leading cause of death in cancer patients. In Brazil, even though low-molecular-weight heparin (LMWH) is the gold standard of care for the management of cancer-associated thrombosis (CAT), its cost limits its use and therefore warfarin is commonly prescribed. Direct oral anticoagulants (DOACs), such as edoxaban, have been introduced as an alternative in this setting. Objective: The aim of this study was to compare the cost-effectiveness of edoxaban with LMWH (Model 1) and warfarin (Model 2) to support clinicians and hospitals when choosing an anticoagulant to manage CAT. Materials and methods: Cost-effectiveness analyses were performed using Markov state-transition models over a timeframe of 5 years, in a hypothetical, 64 years-old patients cancer population with an index VTE event. Transition probabilities, costs, quality-adjusted life years (QALYs) and risk reductions were either derived from the literature, estimated or calculated. A willingness-to-pay limit of 3 Gross Domestic Product (GDP) per head was used. Deterministic and probabilistic sensitivity analyses were performed for robustness. The main outcome of this study was the incremental cost-effectiveness ratio (ICER), expressed as cost per QALY gained. Results: Model 1 base case analysis demonstrated dominance of edoxaban compared to LMWH, with an ICER of 5204.46, representing cost saved per QALY lost. In Model 2, edoxaban was associated with a 736.90 cost increase vs. warfarin, with an ICER of 2541.03. Sensitivity analyses confirmed base-case results. Conclusion: Edoxaban represents a cost-saving alternative to LMWH for the management of CAT and is cost-effective vs. warfarin. Highlights: Edoxaban is a new clinically effective treatment for cancer-associated thrombosis (CAT). Low-molecular weight heparin (LMWH) and warfarin are not optimal treatment options in CAT. We compared the cost-effectiveness of edoxaban vs LMWH and warfarin from a Brazilian payer perspective. Edoxaban is a cost-effective alternative vs. LMWH and also warfarin for the treatment of CAT in Brazil. Edoxaban is a significant cost-saving strategy vs. LMWH for the management of CAT in Brazil.